2016
DOI: 10.1523/jneurosci.1596-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Superior Intraparietal Sulcus Controls the Variability of Visual Working Memory Precision

Abstract: Limitations of working memory (WM) capacity depend strongly on the cognitive resources that are available for maintaining WM contents in an activated state. Increasing the number of items to be maintained in WM was shown to reduce the precision of WM and to increase the variability of WM precision over time. Although WM precision was recently associated with neural codes particularly in early sensory cortex, we have so far no understanding of the neural bases underlying the variability of WM precision, and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…Future work could investigate how the brain representations of visual memories change with age, and whether the effects of context and metacognitive strategies are to support brain representations that are more like those of younger adults, or whether they recruit distinct brain systems or representational mechanisms. A number of neural markers of individual differences in VSTM are available, using EEG (e.g., Sauseng et al, 2009 ; Vogel & Machizawa, 2004 ), MEG (e.g., Honkanen, Rouhinen, Wang, Palva, & Palva, 2015 ; Mitchell & Cusack, 2011 ; Palva, Monto, Kulashekhar, & Palva, 2010 ; Siebenhühner et al, 2016 ), and fMRI (e.g., Ester, Anderson, Serences, & Awh, 2013 ; Galeano Weber, Peters, Hahn, Bledowski, & Fiebach, 2016 ; Linke et al, 2011 ; McNab & Klingberg, 2008 ; Stevens, Tappon, Garg, & Fair, 2012 ; Todd & Marois, 2005 ; Veldsman et al, 2017 ; Vicente-Grabovetsky, Carlin, & Cusack, 2014 ), with some differences reported across age groups (for a review see Sander et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work could investigate how the brain representations of visual memories change with age, and whether the effects of context and metacognitive strategies are to support brain representations that are more like those of younger adults, or whether they recruit distinct brain systems or representational mechanisms. A number of neural markers of individual differences in VSTM are available, using EEG (e.g., Sauseng et al, 2009 ; Vogel & Machizawa, 2004 ), MEG (e.g., Honkanen, Rouhinen, Wang, Palva, & Palva, 2015 ; Mitchell & Cusack, 2011 ; Palva, Monto, Kulashekhar, & Palva, 2010 ; Siebenhühner et al, 2016 ), and fMRI (e.g., Ester, Anderson, Serences, & Awh, 2013 ; Galeano Weber, Peters, Hahn, Bledowski, & Fiebach, 2016 ; Linke et al, 2011 ; McNab & Klingberg, 2008 ; Stevens, Tappon, Garg, & Fair, 2012 ; Todd & Marois, 2005 ; Veldsman et al, 2017 ; Vicente-Grabovetsky, Carlin, & Cusack, 2014 ), with some differences reported across age groups (for a review see Sander et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual working memory (VWM) research has seen a convergence in recent years between cognitive models emphasizing the role of attention to knowledge structures (Cowan, 1988(Cowan, , 1995(Cowan, , 1999 and neurophysiological evidence for the sustained engagement of circuits in posterior cortex involved in the perception of the remembered information (Supèr et al, 2001;Pasternak and Greenlee, 2005;Serences et al, 2009;Sprague et al, 2014;Foster et al, 2016;van Kerkoerle et al, 2017). Among the outstanding questions about the precise mechanisms and boundary conditions of this principle of "sensorimotor recruitment" in working memory (e.g., D'Esposito and Postle, 2015) is understanding the contributions to VWM of the territory of the intraparietal suclus (IPS) vis-a-vis classically defined visual circuits of occipital cortex.…”
Section: Introductionmentioning
confidence: 99%
“…What are the neural mechanisms underlying VWM deficits and distraction effects in SZ? A recent study has identified the superior intraparietal sulcus (IPS) as the cortical region controlling resource allocation variability 42 . SZ patients have also been found the atypical neural processing in this region 43 .…”
Section: Discussionmentioning
confidence: 99%